2015
DOI: 10.1111/asj.12537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre‐slaughter stressor and feeding preventative Chinese medicinal herbs on glycolysis and oxidative stability in pigs

Abstract: A total of 64 5-month-old Pietrain pigs were randomly allocated to four treatments with four replicates per treatment according to body weight. The pigs were fed either a standard corn-soybean meal based control diet (treatments 1 and 2), the standard diet with 1% Lycium barbarum (LB) (treatment 3), or the standard diet with 1% Polygala tenuifolia Willd (PT) (treatment 4). Serum lactic acid and glucose concentrations were increased in stressed pigs (P < 0.05). Addition of the herbs in the diet had no effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
(55 reference statements)
1
13
0
1
Order By: Relevance
“…This result could be due to the different physiological moment of the animals used in our study (end of career) compared to those used in the previous one (rabbits in growth). However, diets supplemented with natural bioactive compounds have not always had an effect on animal growth or on the improvement of the yield at slaughter, as reported by Bai et al and Koné et al [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could be due to the different physiological moment of the animals used in our study (end of career) compared to those used in the previous one (rabbits in growth). However, diets supplemented with natural bioactive compounds have not always had an effect on animal growth or on the improvement of the yield at slaughter, as reported by Bai et al and Koné et al [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors [ 18 , 19 , 20 ], suggested that the beneficial and nutritional properties of goji berries are able to express their action not only at the level of the human or laboratory animals’ microbiota, but also on livestock animals. Menchetti et al have previously conducted studies on does and growing rabbits evaluating the effect of the GBs supplementation on the productive performance [ 21 ] and meat quality [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of the goji berries are mainly studied in laboratory animals such as mice and rats [9,10,13] and only a few trials were conducted using the rabbit [14][15][16] although it is considered a useful experimental animal model [17][18][19][20][21][22]. Moreover, only a limited number of researches evaluated the effects of goji berry on the reproductive and productive performance, other than on the quality of meat, in livestock animals, rabbits included [15,16,[23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…For example, spirulina (Dal Bosco et al, 2014), alfalfa extracts (Dabbou et al, 2018), cauliflower (Perna, Simonetti, Grassi, & Gambacorta, 2019), and some herbs used in traditional Chinese Medicine, such as Zingiber officinale (Mancini, Secci, Preziuso, Parisi, & Paci, 2018), have been evaluated. However, the influence of a dietary supplementation with Lycium barbarum has not been studied yet in rabbit meat quality although it has already produced encouraging results in pigs (Bai et al, 2016).…”
Section: Introductionmentioning
confidence: 99%